Characteristic of Chrome-Tanned and Vegetable-Tanned Goat Garment Leathers - Rosiati, Nur Mutia; Rachmawati, Laili; Udkhiyati, Mustafidah (State Islamic University of Sultan Syarif Kasim Riau, 2024)
ABSTRACT. Chrome tanning material is still widely used in the tanning process for garment leather production. Its use began to be reduced to overcome its negative environment impact. Vegetable tannin of a mimosa and tara combination was used in this study to substitute chrome tanning material. Garment made from vegetable-tanned leather with a ratio mimosa to tara of 5:13 was compared to garments made from chrome-tanned leather, both the production methods and resulting leather characteristics. To obtain garment leather characteristics, chrome-tanned leather requires auxiliary materials and two fatliquoring steps. Vegetable-tanned leather requires more auxiliary materials and fatliquoring steps (3 steps). Physical test results show that chrome-tanned leather gives better tensile strength, elongation, tear strength, and softness that meet with SNI (Standar Nasional Indonesia or Indonesian National Standard). Meanwhile, garments from vegetable-tanned leather exhibit elongation, tear strength, and softness that meet with SNI. However, adding auxiliary materials and fatliquoring steps in the garment-making process from vegetable-tanned leather is still unable to produce the softness, smoothness, and elasticity of a garment from chrome-tanned leather.